Determination of the activity of alpha naphthyl acetate esterase and acid phosphatase of peripheral blood lymphocytes in healty pregnant cattle - Emrah Sur; İbrahim Aydın; Yasemin Öznurlu; Tuğba Telatar (Eurasian Journal of Veterinary Sciences)
This study was performed to determine the effects of pregnancy on the activities of alpha naphthyl acetate esterase (ANAE) and acid phosphatase (ACP-ase) of the peripheral blood lymphocytes in pregnant cattle. Peripheral blood lymphocyte percentages were also estimated. These animals divided into four groups as Control; Trimester I; Trimester II and Trimester III (n= 20 for each group). There was a statistically decreases in the proportions of the ACP-ase (+) lymphocytes in Trimester I and Trimester III. The lowest ANAE (+) T-lymphocytes percentage was determined in Trimester I but the differences between the groups were not statistically important. A dramatic reduction in the percentage of peripheral blood lymphphocytes was recorded in Trimester I (p<0,05) whereas the highest null cell rates were found at the same period. It was concluded that the pregnancy effects the peripheral blood lymphocytes in cattle especially Trimester I.